2008
DOI: 10.1167/iovs.08-1807
|View full text |Cite
|
Sign up to set email alerts
|

HVEM and Nectin-1 Are the Major Mediators of Herpes Simplex Virus 1 (HSV-1) Entry into Human Conjunctival Epithelium

Abstract: HSV-1 entry into HCjE cells is a pH-dependent process that is aided by targeted virus travel on filopodia. HCjE cells express all three major entry receptors, with nectin-1 and HVEM playing the predominant role in mediating entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 28 publications
1
68
0
Order By: Relevance
“…40,41 Cells infected with HSV-1 strain K26GFP exhibit punctate nuclear fluorescence at early times in the replication cycle and at later times during infection, a generalized cytoplasmic and nuclear fluorescence, including fluorescence at the cell membranes can be observed. 40 K26GFP was shown to grow wt virus as well in cell culture.…”
Section: Virusesmentioning
confidence: 99%
“…40,41 Cells infected with HSV-1 strain K26GFP exhibit punctate nuclear fluorescence at early times in the replication cycle and at later times during infection, a generalized cytoplasmic and nuclear fluorescence, including fluorescence at the cell membranes can be observed. 40 K26GFP was shown to grow wt virus as well in cell culture.…”
Section: Virusesmentioning
confidence: 99%
“…Many known protein receptors for HSV-1 entry can be blocked by antibodies, which in turn, blocks viral entry [157,169]. Similar to those receptors, we also found that pAbs against synedecan-1 and syndecan-2 block entry.…”
Section: Discussionsupporting
confidence: 75%
“…However, high affinity interactions (accompanied by conformation changes) may not be blocked by antibodies and therefore, the net effect by combining the antibodies may not be significantly higher than the individual effects. This may be a reason why a near complete blocking of HSV-1 infection by antibodies has been extremely rare even when all gD receptors were blocked [157,169]. Our results, nevertheless, highlight that syndecan-1 and syndecan-2 both play a critical role during HSV-1 entry and that the two HSPGs show detectable differences in their abilities to facilitate infection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, it has been reported that HVEM on nonhematopoietic cells, including mucosal epithelial cells, promotes antipathogen inflammation related to a Th17-type response (31,32,36). Although the cornea and palpebral conjunctiva are known to express HVEM (37,38), it remains unknown whether HVEM is expressed in the retina and uvea (i.e., target tissues in EAU), and if so, whether HVEM in these tissues plays any role in the pathogenesis of EAU. To address this question, we first examined HVEM expression in eye tissues, including the retina and uvea, and found positive staining by Western blot analysis, even though the level of expression was much lower than in the thymus (Supplemental Fig.…”
Section: Hvem On Nonhematopoietic Cells In Dispensable For Eau Pathogmentioning
confidence: 99%